2007
DOI: 10.1024/1421-0185.66.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Fathers of Girls, Fathers of Boys: Influence of Child’s Gender on Fathers’ Experience of, Engagement in, and Representations of Paternity

Abstract: The aim of this study was to examine the influence of child’s gender on several dimensions of paternity: the fathers’ personal experience of paternity, their involvement in child rearing, and their representations. A total of 147 Swiss fathers of 18-month-old children (65 girls and 82 boys) completed questionnaires. The child’s gender had little influence on paternal experience, relationship to the child or relationship with the child’s mother. Globally, the fathers took on few responsibilities which were larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
5
0
3
Order By: Relevance
“…Studies in the United States have found that fathers tend to spend more time with their sons than daughters (Lam et al, 2012; Mammen, 2011; Raley & Bianchi, 2006). A similar son-bias in paternal caregiving has been reported among fathers in Switzerland (Rouyer et al, 2007) and fathers with lower levels of educational attainment in Denmark (Bonke & Esping-Andersen, 2009; Rouyer et al, 2007). A cross-national study on secondary school children across England, Germany, the Netherlands, and Sweden also found that divorced fathers were more likely to have co-parenting arrangements and contact with sons than daughters (Kalmijn, 2015).…”
Section: Introductionsupporting
confidence: 70%
“…Studies in the United States have found that fathers tend to spend more time with their sons than daughters (Lam et al, 2012; Mammen, 2011; Raley & Bianchi, 2006). A similar son-bias in paternal caregiving has been reported among fathers in Switzerland (Rouyer et al, 2007) and fathers with lower levels of educational attainment in Denmark (Bonke & Esping-Andersen, 2009; Rouyer et al, 2007). A cross-national study on secondary school children across England, Germany, the Netherlands, and Sweden also found that divorced fathers were more likely to have co-parenting arrangements and contact with sons than daughters (Kalmijn, 2015).…”
Section: Introductionsupporting
confidence: 70%
“…A likely mechanism by which fathers' parenting stress affects their children's language development is by eroding the quality of fathers' language use during father–child interactions. One possibility for the differential effects of fathers' stress on boys' and girls' language is that fathers interact more often, both verbally and physically, with their boys than with their girls from early infancy (Frascarolo & Zaouche‐Gaudron, 2003 cited in Rouyer et al, ; Manlove & Vernon‐Feagans, ; NICHD Early Child Care Research Network, ; Parke, ; Rouyer et al, ), thus fathers' stress‐ridden interactions with boys likely occur more frequently and have a greater influence on boys' developing language than on that of girls. Another possibility for the gender difference is that girls elicit more language from their fathers despite fathers' stress.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research on fathers' stress has focused on its effects on children's behavioural outcomes; to date, little is known about the effects of fathers' stress‐related interaction qualities with children on children's cognitive and language development. Further, because fathers are found to have more verbal and physical interactions with their boys versus their girls during early childhood (Parke, ; Frascarolo & Zaouche‐Gaudron, 2003 cited in Rouyer, Frascarolo, Zaouche‐Gaudron, & Lavanchy, ; NICHD Early Child Care Research Network, ; Manlove & Vernon‐Feagans, ), there is a need to examine the possibility of child gender differences in the effects of fathers' stress as well. In particular, examining the moderating role of child gender in the effects of fathers' stress on children's, outcomes may elucidate whether the effects of parenting stress are consistently strongest for boys regardless of parent gender.…”
mentioning
confidence: 99%
“…et al, 2007;Rouyer, Frascarolo, Zaouche-Gaudron & Lavanchy, 2007). Assim, o objetivo do presente estudo consistiu em investigar as práticas educativas maternas e paternas, em particular o uso de práticas indutivas, coercitivas e de não interferência aos 24 e 72 meses de vida da criança, examinando as eventuais diferenças entre as práticas relatadas pelas mães e pelos pais.…”
unclassified